Development of Diversity Monopoly Game Smart Board Learning Media to Improve IPAS Learning Outcomes of Grade IV Elementary School Students - Erika Septianing Rustianti; Sri Sami Asih (Jurnal Penelitian Pendidikan IPA, 2025)
Based on the results of the pre-research, the problem was the lack of use of learning media at SDN Sembaturagung 02 which affected the low learning outcomes of students. This study aims to develop, test the feasibility, and effectiveness of the Diversity Monopoly Game Smart Board. This study uses a Research and Development (R&D) approach that refers to the Borg and Gall model. The population in this study was 35 students with 10 small-scale subjects from class IV SDN Sembaturagung 01 and 25 large-scale subjects from class IV SDN Sembaturagung 02. The data collection techniques used were tests (pretest-posttest) and non-tests in the form of observations, questionnaires, interviews, and documentation data. The validation results by media and material expert validators showed that the Diversity Monopoly Game Smart Board met the criteria of being very feasible with a percentage of 90% from media experts and 88.75% from material experts. Based on the results of the pretest-posttest, it is known that the Diversity Monopoly Game Smart Board is quite effective in improving student learning outcomes, indicated by an average increase of 31.68 with an N-Gain test result of 0.6640 which is in the moderate and quite effective category. The responses of teachers and students were very positive with an average percentage of 92% indicating practicality. It can be concluded that the Diversity Monopoly Game Smart Board is feasible, practical, and quite effective in improving the learning outcomes of IPAS subjects on cultural diversity and local wisdom.